Assistance in Legal Counseling Regarding Procedures for Settlement of Land Disputes Through the Legal Authority of Simantek Kuta (in Kuta Rayat Village, Naman Teran District, Karo Regency) - Tarigan, Tetty Marlina; Zarkawi, Ahmad Farhan (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
In social life, the existence of land cannot be denied from all human actions themselves, because land is a place for humans to live and continue their lives. Therefore, land is needed by every member of society so that it can cause disputes between each other. Land disputes are land disputes involving people, community groups, legal entities and the government. Disputed land is land whose ownership is disputed by two parties competing for ownership of the land as regulated in the regulation of the Head of the Indonesian National Land Agency No. 3 of 2011. This research aims to discuss the authority of the Kuta simantek in the current structure of the Karo indigenous community. in ways of resolving land disputes. This research uses legal sociology methods, using analytical descriptive analysis. Secondary data from primary, secondary and tertiary legal sources was collected through library research and field studies.